Mechanical thrombectomy for large vessel occlusion between 6 and 24 h: outcome comparison of DEFUSE-3/DAWN eligible versus non-eligible patients - Tolga D Dittrich; Peter B Sporns; Lilian F Kriemler; Salome Rudin; Anh Nguyen; Annaelle Zietz; Alexandros A Polymeris; Christopher Tränka; Sebastian Thilemann; Benjamin Wagner; Valerian L Altersberger; Ines Piot; et al. (SAGE Journals, 2022)
Background:
The DEFUSE-3 and DAWN trials showed that mechanical thrombectomy (MT) improves the outcome of selected patients with anterior circulation large vessel occlusions (LVO) up to 24 h after stroke onset. However, it is unknown whether only those patients fulfilling the trial inclusion criteria benefit, or whether benefit is seen in a broader range of patients presenting between 6 and 24 h.
Aims:
We determined whether fulfilling the DEFUSE-3 and DAWN selection criteria affects outcomes in MT patients in clinical practice.
Methods:
We reviewed adult patients with LVO treated with MT between 6 and 24 h after stroke onset at five Swiss stroke centers between 2014 and 2021. We compared two groups: (1) patients who satisfied neither DEFUSE-3 nor DAWN criteria (NDND) and (2) those who satisfied DEFUSE-3 or DAWN criteria (DOD). We used logistic regression to examine the impact of trial eligibility on two safety outcomes (symptomatic intracranial hemorrhage [sICH] and all-cause mortality at 3 months) and two efficacy outcomes (modified Rankin Score [mRS] shift toward lower categories and mRS of 0–2 at 3 months).
Results:
Of 174 patients who received MT, 102 (59%) belonged to the NDND group. Rates of sICH were similar between the NDND group and the DOD group (3% vs. 4%, p = 1.00). Multivariable regression revealed no differences in 3-month all-cause mortality (aOR 2.07, 95% CI 0.64–6.84, p = 0.23) or functional outcomes (mRS shift: acOR 0.81, 95% CI 0.37–1.79, p = 0.60; mRS 0–2: aOR 0.91, 95% CI 0.31–2.57, p = 0.85).
Conclusion:
Among adult patients with LVO treated with MT between 6 and 24 h, safety and efficacy outcomes were similar between DEFUSE-3/DAWN eligible and ineligible patients. Our data provide a compelling rationale for randomized trials with broader inclusion criteria for MT.
Keywords: Cardiology; Medicine; 110904 Neurology and Neuromuscular Diseases